Neuroinflammation and iron metabolism after intracerebral hemorrhage: a glial cell perspective - Ju, Jia-Jun; Hang, Li-Hua (Frontiers in Neurology, 2025)
Intracerebral hemorrhage (ICH) is the most common subtype of hemorrhagic stroke causing significant morbidity and mortality. Previously clinical treatments for ICH have largely been based on a single pathophysiological perspective, and there remains a lack of curative interventions. Following the rupture of cerebral blood vessels, blood metabolites activate resident immune cells such as microglia and astrocytes, and infiltrate peripheral immune cells, leading to the release of a series of inflammatory mediators. Degradation of hemoglobin produces large amounts of iron ions, leading to an imbalance of iron homeostasis and the production of large quantities of harmful hydroxyl radicals. Neuroinflammation and dysregulation of brain iron metabolism are both important pathophysiological changes in ICH, and both can exacerbate secondary brain injury. There is an inseparable relationship between brain iron metabolism disorder and activated glial cells after ICH. Glial cells participate in brain iron metabolism through various mechanisms; meanwhile, iron accumulation exacerbates neuroinflammation by activating inflammatory signaling pathways modulating the functions of inflammatory cells, and so on. This review aims to explore neuroinflammation from the perspective of iron metabolism, linking the complex pathophysiological changes, delving into the exploration of treatment approaches for ICH, and offering insights that could enhance clinical management strategies.